(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Investigate the value and change of procalcitonin, lactate, and leukocyte levels with predictive death factors in patients with septic shock. Subjects and methods: Study on 98 patients diagnosed with septic shock treated inpatient and assigned to test procalcitonin, lactate and blood count from 9/2020 to 8/2021. Result: Procalcitonin concentration at time T1 (74.83 ng/mL), the group of survivors was 34.54 ± 22.1 ng/mL and the group of dead was 97.22 ± 41.09 ng/mL; Procalcitonin survival group decreased 33.3% after 24 hours, 62.7% after 48 hours; Procalcitonin mortality group decreased from 1.0% to 0.03% . At the time of T3, the Procalcitonin cut-off value of 35.15 ng/mL (p < 0.01) can predict mortality with a sensitivity of 98.4%; The specificity is 97.1% and the area under the curve is 0.988. Conclusion: Initial procalcitonin levels have a predictive value in mortality in patients with septic shock, and procalcitonin decreases rapidly in patients who respond well to treatment.